2016
DOI: 10.1051/0004-6361/201629776
|View full text |Cite
|
Sign up to set email alerts
|

TOPoS

Abstract: Aims. One of the primary objectives of the TOPoS survey is to search for the most metal-poor stars. Our search has led to the discovery of one of the most iron-poor objects known, SDSS J092912.32+023817.0. This object is a multiple system, in which two components are clearly detected in the spectrum. Methods. We have analysed 16 high-resolution spectra obtained using the UVES spectrograph at the ESO 8.2 m VLT telescope to measure radial velocities and determine the chemical composition of the system. Results. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…There are three CEMP-no binary stars on the main sequence (or close to the turn-off), G77−61 with T eff = 4000 K, SDSS J0140+2344 with T eff = 5703 and log g = 4.7, and SDSS J0929+0238 with T eff = 5894 K and log g = 4.5. Another possibility is that SDSS J0929+0238 is a sub-giant branch star with log g = 3.7, but it is argued by Caffau et al (2016) that the main-sequence solution is more likely (unfortunately the Gaia DR2 parallax for this star is uncertain). One of the CEMP-no binary stars, HE 0219−1739, is at the tip of the giant branch.…”
Section: Hertzsprung-russell Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…There are three CEMP-no binary stars on the main sequence (or close to the turn-off), G77−61 with T eff = 4000 K, SDSS J0140+2344 with T eff = 5703 and log g = 4.7, and SDSS J0929+0238 with T eff = 5894 K and log g = 4.5. Another possibility is that SDSS J0929+0238 is a sub-giant branch star with log g = 3.7, but it is argued by Caffau et al (2016) that the main-sequence solution is more likely (unfortunately the Gaia DR2 parallax for this star is uncertain). One of the CEMP-no binary stars, HE 0219−1739, is at the tip of the giant branch.…”
Section: Hertzsprung-russell Diagrammentioning
confidence: 99%
“…The ranges on the x-and y-axes have been truncated for clarity, however at least the two largest peaks of the distribution are always shown. SDSS J0929+0238(Caffau et al 2016) and SDSS J1341+4741(Bandyopadhyay et al 2018), we have a sample of eleven CEMP-no binary stars.…”
mentioning
confidence: 99%
“…The number of extremely and ultra metal-poor stars (with [Fe/H] < −3.0 and [Fe/H] < −4.0, respectively; Beers & Christlieb 2005) analysed in depth has grown a lot in the last decades thanks to laborious efforts to find and characterise them. There are now ∼10 stars known with intrinsic iron-abundances below [Fe/H] = −4.5 (Christlieb, Wisotzki & Graßhoff 2002;Frebel et al 2005;Norris et al 2007;Caffau et al 2013a;Hansen et al 2014;Keller et al 2014;Allende Prieto et al 2015;Bonifacio et al 2015;Allende Prieto et al 2015;Caffau et al 2016) 1 . Some of the most iron-poor stars display abundance patterns that could bear the imprint of the explosion physics of first supernovae.…”
Section: Introductionmentioning
confidence: 99%
“…The SDSS-based metallicities found by the method of Ludwig et al (2008) are essentially confirmed by the analysis at higher resolution. This method has been very successful and has led to a series of papers that have Article number, page 2 of 14 already been published (Caffau et al 2011a(Caffau et al ,b, 2012(Caffau et al , 2014Bonifacio et al 2015;Caffau et al 2016;Bonifacio et al 2018). The most metal-poor stars are formed out of gas that has been very likely enriched by the ejecta of a single or a few supernovae.…”
Section: Introductionmentioning
confidence: 99%